Professionalism, Workload, and Organizational Climate: Their Impact on Employee Productivity - Manafe, Elbert; Riwu Kore, Jefirstson R; Wadud, Muhammad; Marnisah, Luis (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: The study aims to analyze and prove the influence of professionalism, workload, and organizational climate on employee productivity. Methodology: The research design used is quantitative research. The population of the study was all employees of the Kupang City DPRD Secretariat, totaling 97 employees. All employees became research samples with saturated sampling techniques. The data was obtained through questionnaire interviews (Likert scale), observation, and documentation. The research data consists of primary and secondary data. The data analysis method is multiple linear regression analysis. Results: The results of the study showed a t-value of professionalism of 2.712 > t-table of 1.9852. Workload has a t-value of 3.459 > t-table of 1.9852. The t-value of organizational climate is 11.442 > t-table of 1.9852, and the F-value of 365.582 > F-table of 2.70, which indicates that professionalism, workload, and organizational climate have a positive and significant effect on employee productivity at the Kupang City DPRD Secretariat both partially and simultaneously. The three exogenous variables have a